Breakage of a Pituitary Rongeur Tip while performing Microscopic Lumbar Discectomy and its retrieval: a Case Report - Chaudhary, Rajesh Kumar; Kaucha, Deepak; Barakoti, Ram Krishna; Shrestha, Babu Kaji (Nepal Orthopaedic Association Journal, 2025)
BACKGROUND Microscopic lumbar discectomy is the common surgical procedure performed for lumbar disc herniation. The incidence of instrument breakage during discectomy ranges from 1% for micro-endoscopic discectomy to 3.1% for open discectomy. We report a case of L5-S1 lumbar disc herniation with left sided radiculopathy who was managed surgically. Breakage of the tip of the pituitary rongeur was encountered during microscopic lumbar discectomy. Several attempts were performed to retrieve the metallic foreign body under f luoroscopy, but it migrated more anteriorly and medially. Nephroscope was used with the help of urologist but was not successful. Due to continuous flow of normal saline, it moved more posteriorly and laterally which was removed by bigger size pituitary rongeur. Patient improved clinically and postoperative period is uneventful till 9 months. To our knowledge, only 8 case reports have been published regarding breakage of tip of pituitary rongeur so far.